Declining export prices due to increased competition from NIC: Evidence from Germany and the CEEC - Sebastian Gundel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2007)
In this paper the export demand and supply of German manufacturing industry is estimated for the period 1993:1 through 2005:4. The Johansen (1991, 1994) procedure is applied to estimate the long-run relationship in a VECM. Special attention is pointed on the development of the German export price being exposed to the competitive environment of fast growing countries like Hungary, the Czech Republic and Poland. Since they offer similar high-technology products on international export markets and are gaining market share Germanys export price suffers downward pressure.
Keywords: C32; F10; F14; 330; manufactured exports; new competition; cointegration; VECM; Außenhandelspreis; Industriegüteraußenhandel; Preiswettbewerb; Internationaler Wettbewerb; Schätzung; Deutschland; Ungarn; Tschechische Republik; Schwellenländer